Clinical Manifestations and Complications of von Willebrand Disease - Shahida Mohsin , Maria Aslam , Shabbir Hussain , Shahla Suhail (Journal of Rawalpindi Medical College, 2012)
Background: To describe the clinical presentation and complications of von Willebrand disease(vWD). Methods: In this descriptive study, out of 426 patients,visiting the hemophilia welfare society Lahore, 57 cases of vWD, diagnosed on the basis of clinical features, prolonged bleeding time (BT), prolonged APTT and decreased vWF antigen were enrolled. Results: Most of the patients (49.1%) were diagnosed at less than one year of age while 35% patients were diagnosed between 1-5 years of age and 15.8% were diagnosed at the age of more than 5 years. Family history of bleeding disorder was found in 60%. Common clinical presentation of disease was epistaxis (77.2%), easy bruising (64.9%) and mennorhagia (21.1%). Disease complications were seen in 35% patients. Hepatitis C was the commonest complication (31.6%). Arthropathy was seen in 22.8%. CNS complications and Hepatitis B were seen in 1.8% each. Conclusion: In inherited bleeding disorders patients , with soft tissue bleeds, vWD is the commonest